Penggunaan Media Sosial Sebagai Platform Utama Untuk Branding Digital - Mahis Duhan; Gusti Alfian; Ardiansyah; Refo Altalario Bintang Anugrah; Feriandri Lesmana (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
In today’s digital landscape, social media serves as a vital medium for establishing and enhancing brand image. This research explores how social media functions as a key platform for executing digital branding strategies, with a focus on small and medium-sized businesses as well as organizations aiming to broaden their market reach. Utilizing a qualitative descriptive methodology, the study investigates how content delivery, user engagement patterns, and visual presentation contribute to brand perception on platforms like Instagram, Facebook, and TikTok. The data were sourced from literature studies, field observations, and interviews with socially active SMEs. The results indicate that effective branding in the digital sphere is closely tied to consistent brand messaging, compelling visual content, responsive communication, and alignment with audience demographics. Social media platforms offer more than just communication channels—they enable dynamic interactions and empower users to shape brand stories collaboratively. This paper concludes that social media offers a highly adaptable, cost-effective solution for branding and opens competitive opportunities for SMEs in the digital economy. The study recommends that business actors maximize their social media potential by crafting structured content strategies and communication plans that reflect consumer behavior and current digital dynamics.